Water–Energy–Land–Food Nexus Performance and Regional Inequality Toward Low-Carbon Transition in China - Qi Yao; Hailin Cao; Ruilian Zhang (Land, 2025)
The transition to a low-carbon economy in China necessitates an integrated understanding of the interdependencies within the water–energy–land–food (WELF) nexus. This study evaluates the performance of the WELF nexus across Chinese provinces and examines regional disparities that may hinder or facilitate sustainable development goals. Using a multi-dimensional performance index and spatial econometric analysis, we identified key synergies and trade-offs among resource systems under low-carbon policy scenarios. The results revealed significant regional inequalities in nexus efficiency, with economically developed regions exhibiting higher integration and resource optimization, while less-developed areas face persistent structural challenges. These disparities underscore the need for regionally tailored policy interventions that address localized constraints while promoting cohesive national strategies. Our findings provide critical insights for policymakers aiming to align resource management with China’s climate commitments and sustainable development agenda.